Answer:
[tex]r=\frac{3t}{t-1}[/tex]
Step-by-step explanation:
Making r the subject of formula means that we have to rewrite the equation such that it is in the form of r= ___.
Given: t= [tex]\frac{r}{r-3}[/tex]
Multiply both sides by (r -3):
t(r -3)= r
Expand:
rt -3t= r
Bring terms containing 'r' to one side, the rest to the other:
rt -r= 3t
Factorise r out of the left-hand side:
r(t -1)= 3t
Divide both sides by (t -1):
r= [tex]\bf{\frac{3t}{t-1} }[/tex]
Additional:
For more questions on subject of formula, check out: